2014
DOI: 10.1186/1476-4598-13-89
|View full text |Cite
|
Sign up to set email alerts
|

TFAP2B overexpression contributes to tumor growth and a poor prognosis of human lung adenocarcinoma through modulation of ERK and VEGF/PEDF signaling

Abstract: BackgroundTFAP2B is a member of the AP2 transcription factor family, which orchestrates a variety of cell processes. However, the roles of TFAP2B in regulating carcinogenesis remain largely unknown. Here, we investigated the regulatory effects of TFAP2B on lung adenocarcinomas growth and identified the underlying mechanisms of actions in non-small cell lung cancer (NSCLC) cells.MethodsWe first examined the expression of TFAP2B in lung cancer cell lines and tumor tissues. We also analyzed the prognostic predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
3
25
1
Order By: Relevance
“…This is particularly noteworthy, as recent studies have shown that TFAP2B has a significant role in the development of non-small cell lung cancer through mechanisms that involve VEGF-dependent signaling. 29 Defining when a genomic gain constitutes amplification of a particular gene of interest is a complex issue. There is no universal definition and thus defining amplification is often done on a tumor-bytumor basis.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly noteworthy, as recent studies have shown that TFAP2B has a significant role in the development of non-small cell lung cancer through mechanisms that involve VEGF-dependent signaling. 29 Defining when a genomic gain constitutes amplification of a particular gene of interest is a complex issue. There is no universal definition and thus defining amplification is often done on a tumor-bytumor basis.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF initiates signaling pathways in ECs to promote proliferation, migration, survival and vascular permeability. VEGF inhibitors have been developed, as the overexpression of VEGF is frequently associated with a poorer prognosis in various types of cancer (28,29). Subsequent ELISA and western blot analyses also confirmed the cytokine changes reported in the human angiogenesis array.…”
Section: Discussionmentioning
confidence: 99%
“…TFAP2 proteins are RA‐inducible transcriptional activators (Luscher et al., 1989), and have been shown to play important roles during vertebrate development, cell growth and differentiation (Auman et al., 2002; Moser et al., 1997; Zeng et al., 1997; Zhang et al., 1996). In addition, alterations in TFAP2 expression patterns and both oncogenic and tumor suppressive functions have been described in various cancer entities (Fu et al., 2014; Pellikainen and Kosma, 2007). In neuroblastoma, expression of the TFAP2 gene family member TFAP2B , also known as AP‐2β, has been shown to be associated with low risk disease in small tumor cohorts (Fischer et al., 2006; Thorell et al., 2009).…”
Section: Introductionmentioning
confidence: 99%